Description of a new species and new records of Gerromorpha (Insecta: Hemiptera: Heteroptera) from Panama and Colombia - Rodrigues, Juliana Mourão Dos Santos; Crumière, Antonin Jean Johan; Mondragón-F., Silvia Patricia; Morales, Irina; Khila, Abderrahman; Moreira, Felipe Ferraz Figueiredo (Zootaxa, 2021)
The fauna of semiaquatic bugs (Insecta: Hemiptera: Heteroptera: Gerromorpha) from Panama has been explored mainly between the end of the 19th century and the first half of the 20th century, with few reports since then, whereas that from Colombia has been intensively studied in the last decade. Here, we describe Rhagovelia joceliae Rodrigues & Moreira, sp. nov. (Veliidae: Rhagoveliinae), from Panama. Additionally, new records from these countries are presented for Mesovelia mulsanti White, 1879, Mes. zeteki Harris & Drake, 1941 (Mesoveliidae: Mesoveliinae), Lipogomphus leucostictus (Champion, 1898) (Hebridae: Hebrinae), Hydrometra caraiba Guérin-Méneville, 1857 (Hydrometridae: Hydrometrinae), Platyvelia brachialis (Stål, 1860), Stridulivelia (Stridulivelia) raspa (Hungerford, 1929) (Veliidae: Veliinae), R. elegans Uhler, 1894, R. perija Polhemus, 1997, R. rosensis Padilla-Gil, 2011 (Veliidae: Rhagoveliinae), Euvelia advena Drake, 1957, Microvelia albonotata Champion, 1898, Mi. fantastika Padilla-Gil, 2019, Mi. mimula White, 1879 (Veliidae: Microveliinae), Metrobates laudatus Drake & Harris, 1937, Telmatometra ujhelyii Esaki, 1926 (Gerridae: Trepobatinae), Brachymetra albinervus (Amyot & Serville, 1843) (Gerridae: Charmatometrinae), Potamobates anchicaya Polhemus & Polhemus, 1995 (Gerridae: Cylindrostethinae), Limnogonus hyalinus (Fabricius, 1803), and Tachygerris opacus (Champion, 1898) (Gerridae: Gerrinae).